(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
Rivers and lakes are natural heritage that should be preserved at all cost. The history of human civilisation has proven the importance of rivers and lakes to humans but development activities had changed the water quality status of rivers and lakes. Due to pollution, they are no longer of any use to human beings. This study was conducted to evaluate the changes of water quality in major rivers, lakes and dams in the northern region of Peninsular Malaysia. Sampling was carried out in February 2010 and completed in April of the same year. The sampling consisted of 62 sampling stations located in rivers, lakes and dams in Perlis, Kedah and Penang. Readings were taken based on 11 hydrological and physicochemical parameters and the water quality status was classified under the Interim National Water Quality Standards (INWQS) which tabulated six levels of pollution ranging from moderate to extremely polluted in the order of I, IIA, IIB, III, IV and V. Results from the study show that most readings from the rivers which were located in forested areas and areas that have experienced less development in Kedah and Penang show moderate pollution between Class I and IIA. In urban areas, the rivers are categorised under Class IIB and III while in Perlis, upstream rivers are slightly polluted and categorised under Class IIB and III. However, the pollution level decreases in the middle area but increases gradually as it approaches the urban areas. This study would be useful to planners to ensure development will not interfere with rivers and lakes. As natural heritage, it is of the utmost importance to preserve these rivers.